Allelopatic effects of Waltheria indica L.: Biocontrol potential in ecological restoration (Research, Society and Development, 2021)
In Brazil, most degraded areas are occupied by exotic and invasive species, which require alternatives for their management. We evaluated the allelopathic effects of Waltheria indica in the laboratory from aqueous extracts of leaves and roots on the germination of the species Lactuca sativa L. (lettuce), Urochloa brizantha (Hochst. ex A.Rich.) RDWebster (brachiaria) and Handroanthus chrysotrichus (Mart. ex DC.) Mattos (yellow Ipe). We collected adult one-year-old Waltheria indica shrubs in ecological restoration areas by direct seeding. We used two treatments with aqueous extracts of leaves and roots and a control without extract, with ten repetitions of 10 seeds per treatment, totaling 600 seeds per test species. Germination and use of tetrazolium assays to evaluate the potential respiratory activity of the roots were used. The aqueous extract of W.indica leaves affected the number of germinated seeds of all test species, while the aqueous extract of roots affected only L. sativa and H. chrysotrichus. There were no significant differences between treatments (leaf and root extracts) in species germination. The aqueous extracts of Waltheria indica leaves and roots affected germination and cellular respiration of the studied species, mainly in Lactuca sativa. The identification of W. indica allelopathic compounds may be an initial step so that in the future new bioherbicides are produced from extracts of this species, or even that its seeds can be sown together with non-sensitive native species, aiming for control of exotic species in ecological restoration projects.